2010
DOI: 10.1074/jbc.m110.149393
|View full text |Cite
|
Sign up to set email alerts
|

p300-mediated Acetylation of Histone H3 Lysine 56 Functions in DNA Damage Response in Mammals

Abstract: The packaging of newly replicated and repaired DNA into chromatin is crucial for the maintenance of genomic integrity. Acetylation of histone H3 core domain lysine 56 (H3K56ac) has been shown to play a crucial role in compaction of DNA into chromatin following replication and repair in Saccharomyces cerevisiae. However, the occurrence and function of such acetylation has not been reported in mammals. Here we show that H3K56 is acetylated and that this modification is regulated in a cell cycle-dependent manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
141
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(149 citation statements)
references
References 44 publications
7
141
1
Order By: Relevance
“…Acetylation of histones is tightly regulated during the cell cycle and is up-regulated during the S phase in mammalian cells (28). Thus, the high level of HAT activity in HPSE-high cells could be due to a higher number of cells in S phase than are present in the HPSE-low cells.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation of histones is tightly regulated during the cell cycle and is up-regulated during the S phase in mammalian cells (28). Thus, the high level of HAT activity in HPSE-high cells could be due to a higher number of cells in S phase than are present in the HPSE-low cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Synchronization and Cell Cycle Analysis-HeLa cells were synchronized and harvested at different phases according to the method described previously (36). Briefly, 4 mM thymidine was added to the medium when cells reached 50% confluence.…”
Section: Methodsmentioning
confidence: 99%
“…Using the method of double thymidine block (36), HeLa cells were synchronized at the G 1 /S boundary, and then thymidine was removed using ordinary medium to enable cells to progress through the cell cycle. Cells were harvested subsequently every 2 h (up to 12 h) after release from arrest, and the levels of Plk1, Aurora A, and RSK1 were monitored by immunoblotting as cells progressed through the cell cycle (Fig.…”
Section: Plk1 Effects Rsk1 In Hela Cells In Manner Similar To That Inmentioning
confidence: 99%
“…In addition, human CBP/p300 and yeast Rtt109 are responsible for H3K56 acetylation in vivo and is required for DNA replication and genome stability (Das et al, 2009;Han et al, 2007). It is reported that H3K56 acetylation are reduced initially in response to DNA damage, followed by full renewal of an acetylated state, and H3K56Ac is colocalized with other proteins involved in DNA damage signaling pathways such as phospho-ATM, CHK2, and p53 at the sites of DNA repair (Battu et al, 2011;Tjeertes et al, 2009;Vempati et al, 2010). During the S phase of cell cycle, H3K56Ac is on the newly synthesized histone H3 that is incorporated into chromosomes (Masumoto et al, 2005), and it drives chromatin reassembly and checkpoint recovery after DNA repair with the assistance of histone chaperone Asf1 Driscoll et al, 2007).…”
Section: Acetylationmentioning
confidence: 99%